The enneagram in love eaudiobook A road map for building and strengthening romantic relationships. - Hall, Stephanie Barron (Tantor Media, 2020)
Discover deeper bonds and more intimate connections with the power of the Enneagram The Enneagram is a popular tool for self-discovery, but it can also help enhance romantic relationships. With The Enneagram in Love as your guide, you will learn how to use insights from this motivation-based personality system to improve loving partnerships and create a more fulfilling connection with your significant other. This comprehensive exploration of the Enneagram offers an in-depth examination of the ways each of the nine types behaves in relationships: how they handle intimacy, express themselves, and deal with conflict. Discover the opportunities and challenges that you and your partner will face while also getting realistic, actionable advice for navigating and overcoming tough spots you might encounter. Love like you've never loved before—with a little help from the Enneagram.